2022
DOI: 10.1155/2022/5418376
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms of Defective Copper Metabolism in Diabetic Cardiomyopathy

Abstract: Copper is an essential trace metal element that significantly affects human physiology and pathology by regulating various important biological processes, including mitochondrial oxidative phosphorylation, connective tissue crosslinking, and antioxidant defense. Copper level has been proved to be closely related to the morbidity and mortality of cardiovascular diseases such as atherosclerosis, heart failure, and diabetic cardiomyopathy (DCM). Copper deficiency can induce cardiac hypertrophy and aggravate cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 216 publications
0
18
0
Order By: Relevance
“…Metal dyshomeostasis at various levels of an organism is a common denominator and cause or consequence of many illnesses [ 5 ]. Defective copper regulation mediates cardiovascular damage through two general processes that occur simultaneously in the same individual: elevation of Cu(II)-mediated pro-oxidant stress and impairment of copper-catalyzed antioxidant defense mechanisms [ 4 , 10 ]. Low concentrations of copper ions through coronary perfusion could significantly reduce cardiac function [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal dyshomeostasis at various levels of an organism is a common denominator and cause or consequence of many illnesses [ 5 ]. Defective copper regulation mediates cardiovascular damage through two general processes that occur simultaneously in the same individual: elevation of Cu(II)-mediated pro-oxidant stress and impairment of copper-catalyzed antioxidant defense mechanisms [ 4 , 10 ]. Low concentrations of copper ions through coronary perfusion could significantly reduce cardiac function [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition, distribution and elimination of metal micronutrients, such as iron (Fe) and copper (Cu), are essential for life [ 1 ]. Metabolic diseases such as diabetes, obesity and non-alcoholic fatty liver usually involve the interaction of multiple underlying molecular mechanisms [ 2 , 3 , 4 ]. Multiple lines of evidence have shown that metabolic diseases including obesity and diabetes are usually accompanied by the dysfunctional regulation of various metal ions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a relationship between RA and mitochondria. Copper death is a new mode of cell death that is distinct from iron death and necroptosis, and its related genes include SLC31A1, PDHB, PDHA1, LIPT1, FDX1, DLD, DLST, DBT, LIAS, DLAT, GCSH, ATP7A and ATP7B ( 15 , 16 ). The main mechanisms of copper death are the excessive accumulation of lipoylated mitochondrial enzymes and depletion of Fe-S cluster proteins ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this pathological entity on cardiovascular health (CV) create further public health challenges and remain responsible for the increased prevalence of cardiovascular disease (CVD) [ 1 ]. Beyond coronary artery disease (CAD) progression, DM can precipitate or worsen heart failure (HF) due to multifactorial mechanisms (i.e., the accumulation of advanced glycation end products (AGEs), oxidative stress, inflammatory status impairment, decay of intracellular calcium, changes in microRNAs expression) [ 2 , 3 , 4 ]. Patients with diabetes develop HF at more than two-times the rate of patients without diabetes [ 1 ].…”
Section: Introductionmentioning
confidence: 99%